2018
DOI: 10.1016/j.diii.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

High intensity focused ultrasound: The fundamentals, clinical applications and research trends

Abstract: Diagnostic ultrasound has been clinically used for decades. More recently, high intensity focused ultrasound (HIFU) has been developed for therapeutic use as a non-invasive technique for tissue ablation. HIFU is also being investigated for advanced applications at the cellular level. Under guidance by magnetic resonance or ultrasound imaging, HIFU can achieve precise biological effects in tissue with a high safety profile. In this article, we discuss the basic principles, advantages and limitations of HIFU. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(110 citation statements)
references
References 93 publications
0
109
0
1
Order By: Relevance
“…With ultrasound guidance, HIFU accurately triggers coagulation necrosis at the target lesion without damaging the adjacent normal tissue. Compared to open surgery, HIFU offers fewer complications, quicker recovery, shorter hospitalization and better quality of life [10]. However, previous studies have also shown that approximately 20% of patients had recurrences soon after HIFU ablation [11,12]; thus, it is crucial to explore new therapeutic schedule to achieve lower recurrence rate.…”
Section: Introductionmentioning
confidence: 99%
“…With ultrasound guidance, HIFU accurately triggers coagulation necrosis at the target lesion without damaging the adjacent normal tissue. Compared to open surgery, HIFU offers fewer complications, quicker recovery, shorter hospitalization and better quality of life [10]. However, previous studies have also shown that approximately 20% of patients had recurrences soon after HIFU ablation [11,12]; thus, it is crucial to explore new therapeutic schedule to achieve lower recurrence rate.…”
Section: Introductionmentioning
confidence: 99%
“…HIFU, known as ultrasound hot removal, has been used clinically . By focusing the low‐energy ultrasound into a higher‐energy focus, the tumor tissue is heated to more than 60 °C to form irreversible thermal damage.…”
Section: Tumor Therapymentioning
confidence: 99%
“…Depending on the settings, thermal or mechanical effects can be induced, known as thermal ablation or histotripsy. So far, HIFU is approved by the FDA for six indications, including uterine fibroids, benign and malignant prostate lesions, essential tremor, tremor dominant Parkinson's disease, and bone metastases [162].…”
Section: Status Quomentioning
confidence: 99%